INTERNET OF THINGS FOR FIRE IDENTIFICATION WITH TWO SENSOR ARDUINO - Hafdiarsya Saiyar; Desmulyati Desmulyati; Mohammad Noviansyah (Sean Institute, 2023)
Fire is still a severe problem that has been difficult to overcome from the past until now. The fire trigger is due to electrical short circuits and electrical equipment experiencing electrical short circuits as well as gas leaks. However, with very rapid and massive advances in technology, humans today can create tools to anticipate the danger of fire early. This research aims to develop a fire alarm system to detect fire, smoke and gas. The system will use a combination of fire, smoke and gas sensors to detect the presence of these dangers. In the event of a fire or gas leak, the system will hide the alarm. The system will be designed to be easy to install and use. This device will detect Internet of Things (IoT) based fires, which can connect to a WiFi network and send messages via WhatsApp. This device uses Arduino UNO, MQ2 sensor, Flamer sensor, and WhatsApp as message recipients. The research method used is direct observation of the selected objects, namely in the author's home environment and conducting literature studies related to the Arduino Uno microcontroller. This research aims to create a system that will help increase security against fire hazards and reduce the risk of material damage, such as property and physical injury.